2022
DOI: 10.30570/2078-5089-2022-104-1-50-71
|View full text |Cite
|
Sign up to set email alerts
|

Education and Revolutions (Why Do Some Revolutions Take up Arms while Others Do Not?)

Abstract: Despite the existence of numerous hypotheses about what factors influence protesters’ choice of armed vs. unarmed struggle tactics, today there is a dearth of global, quantitative cross-national studies aimed at identifying the reasons why revolutions take a violent vs. a non-violent form. The article attempts to fill one of the gaps existing here by conducting a crossnational analysis of the relationship between education and the type of revolutionary action. Based on the existing literature, the authors doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Those with lower income and educational attainment are characterized by lower of all forms of participation on average, primarily due to the barriers to participation that education would otherwise help them overcome (Teixeira, 1992), and a general apathetic disposition to the political process (Gaventa, 1982). That said, as past research has shown, societies without high levels of educational attainment are not devoid of political protests, but instead, they are of a qualitatively different form: violent rebelling and rioting (Beissinger, 2022;Sawyer and Korotayev, 2022;Ustyuzhanin et al, 2022).…”
Section: Students Universities and The Propensity For Political Protestmentioning
confidence: 99%
“…Those with lower income and educational attainment are characterized by lower of all forms of participation on average, primarily due to the barriers to participation that education would otherwise help them overcome (Teixeira, 1992), and a general apathetic disposition to the political process (Gaventa, 1982). That said, as past research has shown, societies without high levels of educational attainment are not devoid of political protests, but instead, they are of a qualitatively different form: violent rebelling and rioting (Beissinger, 2022;Sawyer and Korotayev, 2022;Ustyuzhanin et al, 2022).…”
Section: Students Universities and The Propensity For Political Protestmentioning
confidence: 99%